2023
DOI: 10.1159/000530185
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Maternal Immune Activation Induced with the Viral Mimetic Poly I:C on Microglia in Exposed Rodent Offspring

Abstract: Maternal immune activation (MIA) can result from a variety of maternal inflammatory factors, including metabolic disorders, nutritional deficits, infections, and psychosocial stress. MIA has been consistently recognized as a major risk factor for neurodevelopmental disorders, and this association seems to be especially important for viral infections, as viral exposure during pregnancy was associated with a higher risk of developing neurodevelopmental disorders, such as schizophrenia. In MIA, the gestational pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 180 publications
0
3
0
Order By: Relevance
“…As stated in Sect. 2.2.1, although Aβ plaques are the central cause of the synapse loss and cognitive deficit in AD, chronic inflammation has also been implicated in the onset and progression of these AD-related pathologies [ 200 , 201 ]. Novel techniques were designed to understand the role of exacerbated inflammation, by using a viral mimetic polyinosinic:polycytidylic acid (poly I:C).…”
Section: In Vitro and Preclinical Studies For Alzheimer’s And Parkins...mentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in Sect. 2.2.1, although Aβ plaques are the central cause of the synapse loss and cognitive deficit in AD, chronic inflammation has also been implicated in the onset and progression of these AD-related pathologies [ 200 , 201 ]. Novel techniques were designed to understand the role of exacerbated inflammation, by using a viral mimetic polyinosinic:polycytidylic acid (poly I:C).…”
Section: In Vitro and Preclinical Studies For Alzheimer’s And Parkins...mentioning
confidence: 99%
“…Novel techniques were designed to understand the role of exacerbated inflammation, by using a viral mimetic polyinosinic:polycytidylic acid (poly I:C). The poly I:C model is known to achieve an increased Aβ deposition and cognitive deficits in a non-transgenic mouse [ 200 , 201 ]. Additionally, several genetic variants of TREM2 (R47H and R62H) have been associated with an increased risk of developing sporadic AD and are being studied in the AD context [ 202 ].…”
Section: In Vitro and Preclinical Studies For Alzheimer’s And Parkins...mentioning
confidence: 99%
“…Importantly, injection of the RNA virus analogue poly(I:C) into pregnant mice results in behavioral and histological abnormalities in MIA offspring [ 22 , 23 , 24 ]. Previous studies have shown that prenatal poly(I:C) exposure leads to microglia activation in offspring [ 25 , 26 , 27 ]. However, it remains unknown as to how maternal immune activation by pregnancy infection disrupts offspring brain development and function.…”
Section: Introductionmentioning
confidence: 99%
“…The brain's resident immune cells, microglia, are key players in neurodevelopment, and may act as an important link between immune dysregulation in MIA and neurological outcomes [13]. Microglia populate the brain early in development (E9.5) and are replaced slowly, so early perturbations may carry forward [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Microglia populate the brain early in development (E9.5) and are replaced slowly, so early perturbations may carry forward [14][15][16]. In addition to supporting neuronal proliferation and survival [13], microglia play a key role in synaptic development through "pruning" synapses by mechanisms such as phagocytosis and trogocytosis [17][18][19]. Dysfunction in synaptic transmission is a key feature of schizophrenia and ASD, and MIA models recapitulate alterations in synaptic spine density; although, whether density is increased or decreased appears to be sensitive to brain region, sex, and the MIA protocol used [20].…”
Section: Introductionmentioning
confidence: 99%